Bis-macrocyclic ligands with two ferrocenyl end groups, and their tetranuclear Dicopper(I) compounds - Comba, Peter (Inorganic chemistry, 1999)
A series of bismacrocyclic ligands with two ferrocenyl groups, exo/endo-1,1‘:1‘ ‘,1‘ ‘‘-[1,2,4,5-tetrakis(5-aza-2-thiahexa-5-enyl)benzene]bisferrocene (exo/endo-FeBeFe), 1,1‘:1‘ ‘,1‘ ‘‘-[1,2:1‘,2‘-tetrakis(5-aza-2-thiahexa-5-enyl)ethene]bisferrocene (1,2-FeEnFe), 1,1‘:1‘ ‘,1‘ ‘‘-[1,1‘:2,2‘-tetrakis(5-aza-2-thiahexa-5-enyl)ethene]bisferrocene (1,1-FeEnFe), 1,1‘:1‘ ‘,1‘ ‘‘-[tetrakis(5-aza-2-thiahexa-5-enyl)methane]bisferrocene (FeMeFe), and their dicopper(I) compounds have been synthesized and characterized (electrochemistry, IR, NMR and Mössbauer spectroscopy). The molecular structure of endo-FeBeFe has been determined by X-ray structure analysis and the copper(I)-induced discrimination of the exo- and endo-isomers of FeBeFe has been investigated by 1H NMR spectroscopy. The interaction between copper and iron in the tetranuclear compounds is discussed on the basis of the electrochemical and spectroscopic data.
Gesehen am 08.03.2018